Advocacy, Efficacy, and Engagement in an Online Network for Latino Childhood Obesity Prevention. Issue 6 (November 2015) - Ramirez, Amelie G.; Gallion, Kipling J.; Despres, Cliff; Aguilar, Rosalie P.; Adeigbe, Rebecca T.; Seidel, Sarah E.; McAlister, Alfred L.
Salud America! is a national network created to engage Latino researchers, health professionals and community leaders in actions to reduce Latino childhood obesity. An online survey of 148 Salud America! network members investigated relationships between (1) their levels of engagement with the network, (2) self- and collective-efficacy, and (3) behavioral intentions to engage in advocacy for policies that can help reduce Latino childhood obesity. Analyses of these data found that higher levels of Salud America! engagement was associated with collective-advocacy efficacy—greater confidence in organized group advocacy as a way of advancing policies to reduce Latino childhood obesity. A multiple regression analysis found that this sense of collective-efficacy moderately predicted intentions to engage in advocacy behaviors. Salud America! engagement levels were less strongly associated with members' confidence in their personal ability to be an effective advocate, yet this sense of self-efficacy was a very strong predictor of a behavioral intention to advocate. Based on these findings, new online applications aimed at increasing self- and collective-efficacy through peer modeling are being developed for Salud America! in order to help individuals interested in Latino childhood obesity prevention to connect with each other and with opportunities for concerted local actions in their communities.